Researching Electronic System of the SC-920 Control Circuit of the DDL-8700-7 Single Needle Sewing Machine and Application - Nguyen, Thi Lan Huong (JST: Engineering And Technology For Sustainable Development, 2023)
The DDL-8700-7 is a single needle electronic sewing machine that uses a servo motor to drive the main shaft. This sewing machine has advantages such as noiseless, energy saving, automatic thread trimming, reverse feed, wiper, lifting of the needle bar to the highest position when the machine stops... The paper presents the research results of the relationship between the mechanical, electrical and electronic parts of the SC-920 control circuit in the DDL-8700-7 single needle sewing machine; analyzing the operating principle of the SC-920 control circuit electronic system according to each control block. In this study, theoretical and experimental research methods were used to measure, test and evaluate the parameters. The obtained theoretical and experimental research results contribute to building a scientific basis for making test methods and repairing circuits for some electrical and electronic errors in the error code list of SC-920, helping the repairer can identify defects for repair and replacement.